The Effectiveness of Reward and Punishment Strategy on Students’ Motivation in Learning English - Nuri, Mita Amalia; Daristin, Pipit Ertika (Universitas Pahlawan Tuanku Tambusai, 2026)
Low motivation in learning English poses a major challenge in Indonesian elementary schools due to its non-native status and insufficient environmental support. This pre-experimental study examined the effectiveness of reward and punishment strategies to improve fifth-grade students’ English learning motivation. Employing a one-group pretest-posttest design, 33 purposively sampled students from Class 5-D at MI Perguruan Mu’allimat completed a 10-item, 4-point Likert motivation questionnaire adapted from Purmama et al. (2019) with acceptable reliability (Cronbach’s α = 0.823). SPSS analysis showed a significant increase from pre-test (M = 24.91, SD = 3.70, moderate) to post-test (M = 33.52, SD = 3.25, high), confirmed by paired t-test (t = -11.197, df = 32, p 0.001). The strategy effectively boosted motivation through immediate feedback, recognition, and consequences, addressing intrinsic and extrinsic needs via competence, autonomy, and relatedness per Self-Determination Theory. Teachers can apply age-appropriate rewards and constructive punishments to foster engaging, disciplined classrooms that sustain interest in English.